1993
DOI: 10.1063/1.465050
|View full text |Cite
|
Sign up to set email alerts
|

Abinitio study of the potential energy surface of CH4-H2O

Abstract: The potential energy surface of CH4-H2O is calculated through the fourth-order Mo/ller–Plesset perturbation theory. In an attempt to obtain basis-set saturated values of interaction energies the extended basis sets are augmented by bond functions which simulate the effects of high-symmetry polarization functions. The absolute minimum occurs for the configuration involving the C–H-O hydrogen-bond in which O-H points toward one of the faces of the CH4 tetrahedron. The equilibrium C–O separation is equal to 6.8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 59 publications
7
61
1
Order By: Relevance
“…The analysis [65] of the PES for the methanewater complex with the use of the perturbation theory of intermolecular forces indicated the anisotropy, the feature that is believed to distinguish hydrogen bonds from van der Waals complexes. Some evidence for hydrogen bonding in the HOH ... CH 4 structure was obtained in the AIM theoretical study, which revealed a bond path connecting the hydrogen atom of water to the carbon of methane and corresponding (3, 1) bond critical point between these atoms [68].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis [65] of the PES for the methanewater complex with the use of the perturbation theory of intermolecular forces indicated the anisotropy, the feature that is believed to distinguish hydrogen bonds from van der Waals complexes. Some evidence for hydrogen bonding in the HOH ... CH 4 structure was obtained in the AIM theoretical study, which revealed a bond path connecting the hydrogen atom of water to the carbon of methane and corresponding (3, 1) bond critical point between these atoms [68].…”
Section: Introductionmentioning
confidence: 99%
“…Third, the Lennard-Jones parameters are chosen so that the minimum energy of the CH 4 -H 2 O dimer has a value and an oxygen carbon distance close to ab initio calculations at the fourthorder Møller-Plesset (MP4) level (Figure 1). 38 Figure 1 also…”
Section: Potential and Simulation Detailsmentioning
confidence: 99%
“…After application of the BSSE correction, a planar structure in which H 2 lies on the C 2V axis was found to have lower energy. These calculations and also past studies 25,31,79 indicate that BSSE correction to the geometry is particularly important when an electrophilic species approaches the lone pair of oxygen.…”
Section: Discussionmentioning
confidence: 98%
“…[25][26][27][31][32][40][41][42][43]76. In this analysis the interaction energy is decomposed into components of different physical origins, such as electrostatic, dispersion, and exchange repulsion.…”
Section: Analysis Of the Contributions To The Potential Surfacementioning
confidence: 99%
See 1 more Smart Citation